Studying the Factors that Affect the Application of Accounting Standards in Vietnam via SEM Model - Ngoc Hung, Dang (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 33 No 4, 2017)
The factors that affect the application of accounting standards in Vietnam are researched. The Structural Equation Modeling is used after the Cronbach Alpha scales have been verified and the exploratory factors have been analyzed. The research tests relationship between levels and benefits of the applied accounting standards. The research has found that there are 3 factors including characteristics of enterprises, legal system, professional consulting organizations that have a positive relation with the application of accounting standards. It is also indicated that the level of the applied accounting standards has a positive relation with the benefits of the applied accounting standards. Keywords Accounting standard, benefits of applied accounting standards, structural equation modeling. References [1] Choi, F.D., & Meek, G.K., International Accounting, 7th ed., Prentice Hall, New York, 2011. [2] Trần Đình Khôi Nguyên, “Bàn về thang đo các nhân tố phi tài chính ảnh hưởng vận dụng chuẩn mực kế toán trong các doanh nghiệp nhỏ và vừa ở Việt Nam”, Tạp chí Kinh tế & Phát triển, 190 (2013) 1, 55-60. [3] Chow, C.W., & Wong-Boren, “Voluntary ﬁnancial disclosure by Mexican corporations”, The Accounting Review, 62 (1987) 3, 533-541. [4] Cooke, T., “Disclosure in the corporate annual reports of Swedish companies”, Accounting and Business Research, 19 (1991) 74, 113-124. [5] Wallace, R. & Naser, K., “Firm-specific determinants of the comprehensiveness of mandatory disclosure in the corporate annual reports of firms listed on the stock exchange of Hong Kong”, Journal of Accounting and Public Policy, 14 (1995) 4, 311-368. [6] Nguyễn Công Phương, “Về mô hình chuẩn mực - chế độ kế toán của Việt Nam”, Tạp chí Kinh tế & Phát triển, 194 (2013) 1, 31-37. [7] Gray, S. J., “Towards a theory of cultural influence on the development of accounting systems interna- tionally”, Abacus, 24 (1988) 1, 1-15. [8] Meek, G.K., Roberts, C.B., & Gray, S.J., “Factors inﬂuencing voluntary annual report disclosures by U.S., U.K. and Continental European multi-national corporations”, Journal of International Business Studies, 26 (1995) 1, 555-572.